Analysis of Sharia Investment Decisions in Achieving Financial Freedom Among Young People: Case Study of West Halmahera Regency - Noho Ulidam; Ilham Putra Usmayani; Ismail Hi Saiyan; Hasbullah Hajar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The aim of this research is to determine the influence of financial literacy, spiritual benefits and income on investment decisions among young people in West Halmahera Regency, Jailolo District. The method used in this research is a quantitative method. The number of respondents in this research was 50 respondents with an age range of 23-35 years. The objects of this research are young people who live in Jailolo subdistrict, West Halamahera Regency who have active worker status. The sampling technique in this research used purposive sampling. The research results show that the financial literacy variable has a significant influence on investment decisions. So, it can be concluded that a person's understanding or high level of financial literacy will increase a person's investment decisions to invest. Spiritual benefits have a significant influence on investment decisions so that understanding a person's religiosity will provide spiritual benefits by avoiding several things that are haram and prohibited by religion. The income variable also has a significant influence on investment decisions so that a person's income becomes a benchmark for the size of a person's investment and also becomes a factor for someone to invest.